Management of pedagogical supervision and its relationship with the teaching performance of the secondary level of the I.E. N ° 3089 "Los Angeles", Ugel Ventanilla. Callao Region – 2017 - Salvatierra Mattos, Silvia Mercedes (2020)
The objective of the research was: to determine the relationship between the management of pedagogical supervision and the teaching performance of the secondary level of I.E No. 3089 "Los Angeles", UGEL Ventanilla. Callao Region - 2017, and its purpose was to find knowledge regarding the implications in the conduct of educational management. The study was developed in the quantitative approach in the hypothetical deductive method, with the type of basic study of non-experimental cross-sectional design. For data collection, two validated instruments were applied at the discretion of judges and determining their statistical reliability by means of a pilot test and Cronbach's alpha coefficient in an intentional sample of 36 teachers. From the analysis procedures performed, a coefficient of r Spearman =, 712 with a p = .000 value was found, which indicates that the variables have a highly significant linear relationship indicating that pedagogical supervision is positively related to teacher performance, inferring that The better management of pedagogical supervision, the higher the level of teaching performance of the secondary level of EI N ° 3089 "Los Angeles", UGEL Ventanilla. Callao Region-2017.